2016
DOI: 10.1371/journal.pmed.1002119
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Tuberculosis Burden and Notifications in Low- and Middle-Income Countries: A Systematic Review and Meta-analysis

Abstract: BackgroundTuberculosis (TB) case notification rates are usually higher in men than in women, but notification data are insufficient to measure sex differences in disease burden. This review set out to systematically investigate whether sex ratios in case notifications reflect differences in disease prevalence and to identify gaps in access to and/or utilisation of diagnostic services.Methods and FindingsIn accordance with the published protocol (CRD42015022163), TB prevalence surveys in nationally representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

52
282
7
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(353 citation statements)
references
References 63 publications
52
282
7
12
Order By: Relevance
“…There is relatively little research on adherence and retention differentials by sex [8,9], and throughout completion of this SR, randomized evaluations which reported treatment outcomes by sex were rarely found. There is also a need for greater attention to and interventions for conditions which tend to affect men more and exacerbate HIV/AIDS prevention and treatment, and increase men’s morbidity and mortality, such as tuberculosis [131] and substance use [18]. …”
Section: Discussionmentioning
confidence: 99%
“…There is relatively little research on adherence and retention differentials by sex [8,9], and throughout completion of this SR, randomized evaluations which reported treatment outcomes by sex were rarely found. There is also a need for greater attention to and interventions for conditions which tend to affect men more and exacerbate HIV/AIDS prevention and treatment, and increase men’s morbidity and mortality, such as tuberculosis [131] and substance use [18]. …”
Section: Discussionmentioning
confidence: 99%
“…TB prevalence is significantly higher among men than women in low-and middle-income countries. 7 Various international and Indian studies have found positive associations between overcrowding and poor ventilation with higher prevalence of TB. 8,9,10,11 In the present study, a considerable number of patients were exposed to inadequate ventilation [54(46.1%)] while Overcrowding was not observed in the majority of the patients [6(5.1%)].…”
Section: Discussion:-mentioning
confidence: 99%
“…TB prevalence is significantly higher among men than women in low-and middle-income countries. 6 A WHO technical meeting at Cape Town in July 2008 concluded that there was sufficient evidence for a causal impact of alcohol on TB incidence and on worsening the disease. 7 A systematic review to assess the association between alcohol use, alcohol use disorders and Tuberculosis (TB) found that heavy alcohol use strongly influences both the incidence and the outcome of the disease and was found to be linked to altered pharmacokinetics of medicines used in treatment of TB, higher rate of re-infection, higher rate of treatment defaults and development of drugresistant forms of TB.…”
Section: Discussionmentioning
confidence: 99%